Biological screening of Amoora rohituka for bioactive principles (University Journal of Zoology, Rajshahi University, 2007)
Key words: Amoora rohituka; biological screening; pesticidal; pharmacological Univ. j. zool. Rajshahi Univ. Vol.24, 2005. pp. 23-26